Till the clouds roll by [videorecording (DVD)] - Kern, Jerome, 1885-1945 (Frank Sinatra collection (Turner Entertainment Co.)., 2008)
A musical based on the life of American Broadway pioneer Jerome Kern, featuring renditions of the famous songs from his musical plays by contemporary stage artists, including a condensed production of his most famous show, Showboat.